Multi-Point Interactions with Immersive Omnidirectional Visualizations in a Dome - Benko, Hrvoje; Wilson, Andy (ITS '10 ACM International Conference on Interactive Tabletops and Surfaces, 2010)
This paper describes an interactive immersive experience using mid-air gestures to interact with a large curved display: a projected dome. Our Pinch-the-Sky Dome is an immersive installation where several users can interact simultaneously with omnidirectional data using freehand gestures. The system consists of a single centrally-located omnidirectional projector-camera unit where the projector is able to project an image spanning the entire 360 degrees and a camera is used to track gestures for navigation of the content. We combine speech commands with freehand pinch and clasping gestures and infra-red laser pointers to provide a highly immersive and interactive experience to several users inside the dome, with a very wide field of view for each user. The interactive applications include: 1) the astronomical data exploration, 2) social networking 3D graph visualizations, 3) immersive panoramic images, 4) 360 degree video conferencing, 5) a drawing canvas, and 6) a multi-user interactive game. Finally, we discuss the user reactions and feedback from two demo events where more than 1000 people had the chance to experience our work.